ChatGPT Acceptance and Use by Generation Z Pre-service Mathematics Teachers - Lestari, Yusfa; Tari, Suci Rizkina; Ramadhani, Widya Putri; Qudratuddarsi, Hilman (LPPM Universitas Bina Bangsa, 2025)
In today’s digital era, educational technology—particularly AI tools like ChatGPT—offers innovative solutions to enhance mathematics education. This study explores how Gen-Z pre-service mathematics teachers accept and use ChatGPT, guided by TPB and UTAUT2 frameworks, while also examining the roles of gender and year of study in shaping their behavior. This quantitative study used a cross-sectional survey with 157 Gen-Z pre-service mathematics teachers, selected via convenience sampling. Data were gathered using a validated questionnaire based on UTAUT, showing high reliability (α = 0.97). Analysis involved descriptive statistics, Pearson correlation, t-tests, and ANOVA to examine ChatGPT acceptance and use by gender and year of study. Descriptive statistics confirmed normal distribution, supporting parametric tests. Pearson coefficients revealed strong, significant correlations between behavioral intention and variables like social influence (r = 0.785) and perceived behavioral control (r = 0.777). Actual ChatGPT use was most correlated with perceived behavioral control (r = 0.784) and attitude (r = 0.738). All predictors, including performance expectancy, effort expectancy, and hedonic motivation, showed positive, significant relationships, supporting the relevance of UTAUT 2 and TPB frameworks in explaining ChatGPT adoption in educational contexts.